2021
DOI: 10.1016/j.jmii.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnosis of COVID-19 in China: A review of challenging cases and analysis

Abstract: Since the initial emergence of coronavirus disease 2019 (COVID-19) in Wuhan, Hubei province, China, a rapid spread of the disease occurred around the world, rising to become an international global health concern at pandemic level. In the face of this medical challenge threatening humans, the development of rapid and accurate methods for early screening and diagnosis of COVID-19 became crucial to containing the emerging public health threat, and prevent further spread within the population. Despite the large n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…The current diagnosis of COVID-19 depends on nucleic acid amplification tests, and recently, many new methods such as loop-mediated isothermal amplification or CRISPR-based assays were developed. The serologic tests using the antigen/antibody of SARS-CoV-2 was also introduced and used for specific purpose or limited circumstance [ 5 7 ]. In particular, reverse-transcription quantitative real-time polymerase chain reaction (RT-qPCR) to identify the target gene of SARS-CoV-2 is a common diagnostic method performed from the early stage of the pandemic in many clinical laboratories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current diagnosis of COVID-19 depends on nucleic acid amplification tests, and recently, many new methods such as loop-mediated isothermal amplification or CRISPR-based assays were developed. The serologic tests using the antigen/antibody of SARS-CoV-2 was also introduced and used for specific purpose or limited circumstance [ 5 7 ]. In particular, reverse-transcription quantitative real-time polymerase chain reaction (RT-qPCR) to identify the target gene of SARS-CoV-2 is a common diagnostic method performed from the early stage of the pandemic in many clinical laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, RT-qPCR is a validated, sensitive molecular diagnostic tool that is used to detect infectious pathogens. However, during massive testing for COVID-19, several studies discussed the concern of false-negative results using RT-qPCR [ 5 , 13 16 ]. Therefore, more sensitive and accurate diagnostic tools are required.…”
Section: Introductionmentioning
confidence: 99%
“…The common symptoms and demises are informed by China. From the entire figure of positive cases, 79,968 infected patients have been recognized in China [39]. It has been found that the clinical characteristics of 1,099 numbers of COVID-19 patients, where the median incubation period time was approximately 3 days, basically the range is 0-24 days, the average period from the development of the symptoms to death was approximately 14 days [40].…”
Section: The Epidemiology Of Novel Coronavirusmentioning
confidence: 99%
“…In the community, the main measure for interrupting the transmission of the disease is the isolation of the infected individuals. For example in China, the decision was taken by Chinese medical authorities to quarantine suspected individuals for 14 days and isolated infected people [39]. Till now there is doubt of the virus's origin some says it came from animals like a bat [73], others say it came from snakes [74], so it is necessary to immediately stop eating these animals and stop coming in close contact with these animal's fluid and or tissues.…”
Section: Prevention and Control Strategies Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation